Engineering Pichia pastoris for improved NADH regeneration: A novel chassis strain for whole-cell catalysis - Geier, Martina; Brandner, Christoph; Strohmeier, Gernot A.; Hall, Mélanie; Hartner, Franz S.; Glieder, Anton (Beilstein Journal of Organic Chemistry, 2015)
Many synthetically useful reactions are catalyzed by cofactor-dependent enzymes. As cofactors represent a major cost factor, methods for efficient cofactor regeneration are required especially for large-scale synthetic applications. In order to generate a novel and efficient host chassis for bioreductions, we engineered the methanol utilization pathway of Pichia pastoris for improved NADH regeneration. By deleting the genes coding for dihydroxyacetone synthase isoform 1 and 2 (DAS1 and DAS2), NADH regeneration via methanol oxidation (dissimilation) was increased significantly. The resulting Δdas1 Δdas2 strain performed better in butanediol dehydrogenase (BDH1) based whole-cell conversions. While the BDH1 catalyzed acetoin reduction stopped after 2 h reaching ~50% substrate conversion when performed in the wild type strain, full conversion after 6 h was obtained by employing the knock-out strain. These results suggest that the P. pastoris Δdas1 Δdas2 strain is capable of supplying the actual biocatalyst with the cofactor over a longer reaction period without the over-expression of an additional cofactor regeneration system. Thus, focusing the intrinsic carbon flux of this methylotrophic yeast on methanol oxidation to CO2 represents an efficient and easy-to-use strategy for NADH-dependent whole-cell conversions. At the same time methanol serves as co-solvent, inductor for catalyst and cofactor regeneration pathway expression and source of energy.
Keywords: bioreduction; cofactor regeneration; dihydroxyacetone synthase; methanol utilization pathway; whole-cell biotransformation

(untitled) - Johanson, T.; Katz, M.; Gorwa-Grauslund, M. F. (FEMS Yeast Res., 2005)

(untitled) - Winkler, C.; Tasnádi, G.; Clay, D.; Hall, M.; Faber, K. (J. Biotechnol., 2012)

Biosystems Engineering I - Weckbecker, A.; Gröger, H.; Hummel, W. (Regeneration of Nicotinamide Coenzymes: Principles and Applications for the Synthesis of Chiral Compounds, 2010)

(untitled) - Duetz, W. A.; Beilen, J. B.; Van Witholt, B. (Curr. Opin. Biotechnol., 2001)

(untitled) - Katz, M.; Sarvary, I.; Frejd, T.; Hahn-Hägerdal, B.; Gorwa-Grauslund, M. F. (Appl. Microbiol. Biotechnol., 2002)

(untitled) - Baerends, R. J. S.; De Hulster, E.; Geertman, J.-M. A.; Daran, J.-M.; van Maris, A. J. A.; Veenhuis, M.; van der Klei, I. J.; Pronk, J. T. (Appl. Environ. Microbiol., 2008)

(untitled) - Schroer, K.; Luef, K. P.; Hartner, S. F.; Glieder, A.; Pscheidt, B. (Metab. Eng., 2010)

(untitled) - Cregg, J. M.; Cereghino, J. L.; Shi, J.; Higgins, D. R. (Mol. Biotechnol., 2000)

(untitled) - Ahmad, M.; Hirz, M.; Pichler, H.; Schwab, H. (Appl. Microbiol. Biotechnol., 2014)

(untitled) - Engelking, H.; Pfaller, R.; Wich, G.; Weuster-Botz, D. (Tetrahedron: Asymmetry, 2004)

(untitled) - Das, S.; Glenn, J. H., IV; Subramanian, M. (Biotechnol. Prog., 2010)

(untitled) - Abad, S.; Nahalka, J.; Bergler, G.; Arnold, S. A.; Speight, R.; Fotheringham, I.; Nidetzky, B.; Glieder, A. (Microb. Cell Fact., 2010)

(untitled) - Geier, M.; Braun, A.; Emmerstorfer, A.; Pichler, H.; Glieder, A. (Biotechnol. J., 2012)

(untitled) - Yan, J.; Zheng, X.; Li, S. (Bioresour. Technol., 2014)

(untitled) - Wriessnegger, T.; Augustin, P.; Engleder, M.; Leitner, E.; Müller, M.; Kaluzna, I.; Schürmann, M.; Mink, D.; Zellnig, G.; Schwab, H.; Pichler, H. (Metab. Eng., 2014)

(untitled) - Hartner, F. S.; Glieder, A. (Microb. Cell Fact., 2006)

(untitled) - De Schutter, K.; Lin, Y.-C.; Tiels, P.; Van Hecke, A.; Glinka, S.; Weber-Lehmann, J.; Rouzé, P.; Van de Peer, Y.; Callewaert, N. (Nat. Biotechnol., 2009)

(untitled) - Krainer, F. W.; Dietzsch, C.; Hajek, T.; Herwig, C.; Spadiut, O.; Glieder, A. (Microb. Cell Fact., 2012)

(untitled) - Reuß, O.; Vik, A.; Kolter, R.; Morschhäuser, J. (Gene, 2004)

(untitled) - Näätsaari, L.; Mistlberger, B.; Ruth, C.; Hajek, T.; Hartner, F.; Glieder, A. (PLoS One, 2012)

(untitled) - Broach, J. R.; Guarascio, V. R.; Jayaram, M. (Cell, 1982)

(untitled) - González, E.; Fernández, M. R.; Larroy, C.; Solà, L.; Pericàs, M. A.; Parés, X.; Biosca, J. A. (J. Biol. Chem., 2000)

(untitled) - Lin-Cereghino, J.; Wong, W. W.; Xiong, S.; Giang, W.; Luong, L. T.; Vu, J.; Johnson, S. D.; Lin-Cereghino, G. P. (BioTechniques, 2005)

(untitled) - Weis, R.; Luiten, R.; Skranc, W.; Schwab, H.; Wubbolts, M.; Glieder, A. (FEMS Yeast Res., 2004)

(untitled) - Abad, S.; Kitz, K.; Hörmann, A.; Schreiner, U.; Hartner, F. S.; Glieder, A. (Biotechnol. J., 2010)